Tuberculosis-related awareness among people living in rural areas of - Ghaffari, Mohtasham; Moradi, Mansoureh; Mehrabi, Yadollah (Archives of Advances in Biosciences, 2015)
Tuberculosis is an infectious disease that caused by Mycobacterium Tuberculosis (TB). Despite the implementation of free treatment, detection rate of TB remains low. Lake of awareness is a main reason for not expressing symptoms in patients. The study aimed to determine the level ofawareness about TB among rural areas of Gorgan. This study was cross-sectional research which was conducted in 2014-2015 in Gorgan villagers (age <?mso-application progid="Word.Document"?>12â‰¥15, ’> non-TB). These individuals were selected by two-staged cluster sampling. The total sample size was 672. The data collection instrument was a researcher-made questionnaire. Face& content validity and also test-retest method were used for validity and reliability, respectively. Participation of individuals in this study was voluntary and with informed consent. The collected data was analyzed using SPSS 16 software. Findings analysis by independent Sample T-Test and Anova test. The mean age of respondents was <?mso-application progid="Word.Document"?>12 33Â±1.17’> . The mean score of villagers’ awareness was <?mso-application progid="Word.Document"?>1230.95Â±6.16’> . The awareness level of 330 participants (49.1%) was high. There was a significant difference between awareness and some variables such as literacy level and age (p<0.05). There wasn’t a significant difference between awareness and gender, family size, history of morbidity, and ethnicity. According to results of this study, Level of villagers’awareness about TB was high, but they lacked awareness on some aspects like the ways of transmission and virulence of disease. It seems that increasing awareness and surveying of influent factors on awareness in people who have TB symptoms is necessary.